Pengembangan Wisata Grojogan Londo melalui Lagu Kreasi sebagai Media Promosi - Mardianto, M. Fariz Fadillah; Pusporani, Elly; Amelia, Dita; Rani, Lina Nugraha; Siregar, Naufal Ramadhan Al Akhwal; Simamora, Antonio Nikolas Manuel Bonar (Universitas Nusantara PGRI Kediri, 2024)
Tourism villages are a form of implementation of community-based and sustainable tourism development. Grojogan Londo Tourism has its signature song entitled